Examining the impact of luxury brand's social media marketing on customer engagement using big data analytics and natural language processing / Elvina Let - Let, Elvina (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
This article was chosen because big data was utilized to examine the influence of luxury brand social media marketing activities on customer engagement. This study studied the impact of luxury brand social media activities concentrating on entertainment aspects, engagement, trends, and adaption on customer loyalty with brand-related social media materials. The usage of social media in the business industry is growing increasingly popular since it provides numerous benefits and readily draws the interest of buyers both outside and inside the country. As a result, the usage of social media delivers several advantages and benefits to a company, manufacturing, and business.